Numerical analysis of hydrogen recombination on a vertical flat plate catalyst - Dae-Hyun Kim; Youngsu Na; Dong-Wook Oh (Results in Engineering)
This study conducts a computational fluid dynamics (CFD) analysis to assess passive autocatalytic recombiners (PARs) for mitigating hydrogen risks in severe accidents. We modeled hydrogen-air mixtures' thermal-fluid dynamics and chemical reactions, comparing single-step reaction rate models with detailed chemical mechanisms on platinum-coated catalyst plates. Results indicate that the simplified single-step model accurately predicts hydrogen recombination on Pt surfaces. Incorporating radiative heat transfer was essential; neglecting it led to significant overestimations of catalyst plate temperatures and hydrogen removal rates. While CFD results aligned with experimental trends from the REKO-3 apparatus, discrepancies arose due to overestimated recombination rates. These findings highlight the importance of precise chemical and thermal modeling in optimizing PAR design, enhancing hydrogen reduction efficiency, and minimizing auto-ignition risks. The validated CFD model offers valuable guidance for improving hydrogen removal efficiency of PARs during severe accidents.